Molecular Dynamics Simulations of Biocorona Formation - Li, Rongzhong; Stevens, Cody A.; Cho, Samuel S. (Modeling, Methodologies and Tools for Molecular and Nano-scale Communications, 2017)
The development and advancement of nanomedicine has opened up many exciting, new applications of nanoparticles such as sensing, imaging, delivery, and therapy. However, their ability to readily enter cells and organelles that allow these nanomedical applications also opens up the possibility of unintended adverse nanotoxicity. The interaction between nanoparticles and biomolecules results in biocorona formation on the nanoparticle surface that is very different from adsorption of biomolecules on a flat surface. It remains a great challenge to understand the applications and risks associated with nanoparticles being in contact with biological systems beyond experimental methods that have limited resolution of the interactions and conformational changes involved. Recently, biomolecule-nanoparticle molecular dynamics (MD) simulations are becoming a viable approach for a detailed view of biocorona formation. In this review, we present the advantages and challenges of several MD simulation approaches for the study of biomolecule-nanoparticle interactions. In particular, we argue for the development of GPU-optimized MD simulations as a critical step in the study of biocorona formation. We discuss recent successes on how integrated computational and experimental studies are important to establish how the structure and functions of biomolecules are affected by nanoparticle interactions with the biomolecules.